A critical analysis of trends in student-centric engineering education and their implications for learning - Pears, Arnold; Nylen, Aletta; Daniels, Mats (2016 IEEE Frontiers in Education Conference (FIE), 2016)
Student-centric education has emerged as a dominant aspect of Higher Education policy over the last two decades. Much has been written about the benefits of student active educational approaches, and applied educational research, for instance the meta-study of Hattie, places emphasis on student-centric learning practices that enhance achieved learning outcomes. Most existing studies have been evaluations of single courses. In contrast this study focusses on the complete study context of the learner, who typically is in the situation of reading two or three courses simultaneously. Our primary goal in this paper is to explore potential challenges as we attempt to scale up active learning to encompass the full curricula. We use a mixture of interview and survey data collected from staff, combined with course schedules and student input to explore some of the potential implications of mandating a student-centric approach over an entire curriculum.